Bioclimatic modeling for the prediction of the suitable regional geographical distribution of selected bright-spored myxomycetes in the Philippine archipelago (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Limbo-Dizon JE, Almadrones-Reyes KJ, Macabago SAB, Dagamac NHA. 2022. Bioclimatic modeling for the prediction of the suitable regional geographical distribution of selected bright-spored myxomycetes in the Philippine archipelago. Biodiversitas 23: 2285-2294. Myxomycetes communities in the Philippines have been well studied in terms of diversity patterns projected by their enigmatic fructifications. To predict potential suitable geographical distributions of three different bright-spored myxomycetes with known variations in its occurrences, namely, Arcyria cinerea, Perichaena depressa, and Hemitrichia serpula, species distribution modeling was utilized. Three different modeling approaches employing MaxEnt were performed in this study and have calculated high model performances based on the AUC values generated (0.778-0.873). In all of the modeling approaches, the three myxomycetes species were predicted to have an expansion of their localized fundamental niches pointing to the influence of isothermality (BIO3) as an important macroclimatic predictor for modeling approaches 1 and 2. Highly suitable habitats for the three bright-spored species were discovered primarily in terrestrial landscapes on the regions of Luzon Island, as well as in small parts of the Visayas and Mindanao Islands. The predicted models in this study do not tell missing geographical information but rather may use as tools for the exploration of potentialities, such as understanding the possible distribution patterns of the three bright-spored myxomycetes species in the Philippines. This can serve as a useful baseline to enhance the conservation efforts for most habitats in the country that are directly affecting microbial communities due to rampant habitat loss and rapid urbanization.